Uma unidade didática para o ensino de inglês: percepção de alunos e professora - Nogueira, Andrea Patrícia (2005)
The aim of this research is to investigate how a teaching material prepared by the teacher-researcher can contribute to the learning process of a group of students. This material was produced in a course offered to teachers of public schools called A Formação Contínua do Professor de Inglês: um Contexto para a Reconstrução da Prática and was elaborated according to the teaching-learning and language approaches suggested by Parâmetros Curriculares Nacionais Língua Estrangeira (1998). This case study examined students perceptions about that material and their learning, as well as the perceptions of the teacher-researcher. The theoretical bases for this study are the development of the reflective teacher proposed by Schön (1992, 2000), Parâmetros Curriculares Nacionais - Língua Estrangeira and Ensino Médio (1998 and 1999) and the sociointeractionist teaching-learning approach suggested by Vygotsky (1987, 1991), as well as some criteria presented for evaluating (Cunningsworth, 1984) and preparing (Ramos, 2004) EFL materials. As a reflection on my daily practice as a teacher, this study helped me to think critically about my role as a teacher and about my students practice. This research also helped students to reflect on their own learning. The results of the analyses helped to observe that the approaches of the Parâmetros for learning a foreign language are meaningful not only to the material analysed here but to any kind of published or unpublished EFL material